Anatomic Variation of Sacral Mesh Attachment During Minimally Invasive Sacrocolpopexy. Issue 4 (3rd April 2023) - Glass Clark, Stephanie; Dang, Rachel; Bonnet, Sarah; Zyczynski, Halina M.; Giugale, Lauren
Abstract : Importance: Although anatomic level of mesh attachment to the sacrum varied during minimally invasive sacrocolpopexy with a large proportion above S1, this was not associated with pelvic organ prolapse recurrence. Objective: This study aimed to describe the anatomic level of sacral mesh attachment and its association with prolapse recurrence after minimally invasive sacrocolpopexy. Study Design: This study included a retrospective cohort of women who underwent minimally invasive sacrocolpopexy with subsequent abdominal and pelvic imaging (magnetic resonance imaging or computed tomography) between 2010 and 2019 at a single academic institution. Anatomic level of attachment was determined by a radiologist. Prolapse recurrence was defined as a composite of self-reported bulge symptoms, any prolapse measure beyond the hymen, and any retreatment with pessary or surgery. χ 2 Tests were used for comparative outcomes. Results: Analyses included 212 women. The mean ± SD age was 58.8 ± 9.9 years, the majority have preoperative stage III/IV prolapse (81.1%), and the median follow-up was 269 days (interquartile range, 57–825 days). Mesh was attached using titanium tacks (n = 136 [64.2%]) and suture (n = 76 [35.8%]) at the level of the L5-S1 intervertebral space (n = 113 [53.3%]) or overlying S1 (n = 89 [42.0%]).The surgical approach was significantly associated with attachment location with a greater proportion of laparoscopy cases demonstrating mesh attachment above S1 (85 [62.5%] vs robotically, 30 [39.5%]; P < 0.01). Dichotomized level of attachment was not associated with composite prolapse recurrence (above S1, n = 18 [22.2%] vs below S1, n = 24 [24.7%]; P = 0.69) or any compartment recurrence ( P ≥ 0.36). Conclusions: Mesh was primarily attached to the anterior longitudinal ligament at the level of the L5-S1 intervertebral space or S1. Level of mesh attachment was not associated with composite prolapse recurrence.